2022
DOI: 10.3390/ijerph19137918
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Fertility: What We Can Learn from an Intergenerational Mouse Obesity Model

Abstract: The aim of this study was to evaluate the effects of being overweight on the ability to conceive, fertilization rate, and in vivo development of embryos in regularly cycling, spontaneously ovulating, and naturally mated female mice. The study was based on statistical analysis of data collected during 14 experiments with identical design, performed on 319 control and 327 obese mice, developed in an intergenerational model of obesity induction which eliminates the impact of aging and high-fat feeding. Six-week-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…The literature describes disaccording opinions about fat content or overweight and lower/higher fertility [ 12 , 35 , 36 , 37 ], which we analyzed in our superior fertile mouse lines. The focus of the present study was to investigate whether the hormonal alterations found in fertility lines can translate into a higher body fat content compared to the control and how it can be connected with their higher ovulation rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature describes disaccording opinions about fat content or overweight and lower/higher fertility [ 12 , 35 , 36 , 37 ], which we analyzed in our superior fertile mouse lines. The focus of the present study was to investigate whether the hormonal alterations found in fertility lines can translate into a higher body fat content compared to the control and how it can be connected with their higher ovulation rate.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid panel in the liver analyzed by heatmap and PCA (provided on request) again shows clusters by line, with FL1 revealing the largest differences, including higher OA and a lower AA, DHA, and AA/EPA ratio. As higher levels of SFAs can cause more severe oxidative stress but higher levels of unsaturated FAs cause serious lipid accumulation [ 38 ], this could play a role in their hepatomegaly together with the higher plasma levels of insulin found earlier [ 14 , 35 , 39 ]. Moreover, the FL1 line is the only one with lower fat content in plasma than the control, which could be one of the reasons why it is a healthy mouse line, even showing an enlarged liver.…”
Section: Discussionmentioning
confidence: 99%